Raising Fisheries Development Program Evaluation in The District Lingga Riau Islands Province - Desi Waryanti; Kismartini Kismartini; Triyuniningsih Triyuniningsih (Program Pascasarjana Universitas Negeri Makassar, 2019)
This study aimed to analyze the evaluation of aquaculture development program in the District Lingga Riau Islands province with output policy indicators and policy outcomes. This research is a descriptive qualitative research. Research site located in the District Lingga Riau Islands province with informants (1) Head aquaculture Marine and Fisheries Agency of Riau Islands province; (2) The chairman, secretary and members of the technical team; (3) Extension of fishery labor contract; (4) The Board pokdakan, then the secondary data, documents, and statistical data. Collection technique used is the technique of in-depth interviews (in-depth interview), observation, documentation, and literature. Engineering validation test data in this study using the technique of triangulation of data, with data analysis techniques of data reduction, data presentation, and draw conclusions (verification). Results showed that the implementation of the program is not maximized especially at the stage of monitoring, coaching and mentoring. Then the program implementation performance is still low. Advice can be given is to improve the monitoring system, the appointment of a companion with consideration of domicile, and coaching and training routine.